Topology optimization and lightweight design of engine hood material for SUV - Tang Youming; Hong Weipeng; Song Mingyang (Functional Materials, 2016)
Based on a 3D model of SUV hood, the mechanical properties analysis was conducted under four different working conditions by using OPTISTRUCT software, and the inner panel of engine hood was topology optimized under the uncertainly conditions. Based on the results of topology optimization, the structure of the inner panel was improved to gain a newly structure of the engine hood, and verified its comprehensive mechanical properties to satisfy realistic engineering and technological requirements. On this basis, three kinds of lightweight materials were selected as the alternative materials for the engine hood. Finally the comprehensive mechanics performance of engine hood was contrasted between pre-optimized and post-optimized. The research results showed that high strength steel is the top priority material for the SUV engine hood which topology post-optimized.